2012
DOI: 10.3109/14767058.2012.717126
|View full text |Cite
|
Sign up to set email alerts
|

Performing discovery-driven neonatal research by transcriptomic analysis of routinely discarded biofluids

Abstract: Objective To perform discovery-driven research on the neonatal salivary and cord blood transcriptomes. Methods Two separate cohorts of infants were enrolled in this study. In one, cord blood (n = 10) and in the other, saliva samples (n = 10) were collected at term gestation. Total RNA was extracted, amplified and hybridized onto Affymetrix HG U133a gene expression microarrays. Following normalization, genes expressed in the highest quintile (≥ 80%) across all subjects in each biofluid were analyzed with Inge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Adult research has shown a 28% concordance between proteins found in saliva and plasma 36 . Similarly, there is a 38% concordance of gene transcripts detectable in whole saliva and whole blood in the newborn 37 . Thus, saliva truly is a ‘window into the body’ and an ideal body fluid for analysis in the neonate.…”
Section: Salivary Transcriptomics: Overviewmentioning
confidence: 86%
“…Adult research has shown a 28% concordance between proteins found in saliva and plasma 36 . Similarly, there is a 38% concordance of gene transcripts detectable in whole saliva and whole blood in the newborn 37 . Thus, saliva truly is a ‘window into the body’ and an ideal body fluid for analysis in the neonate.…”
Section: Salivary Transcriptomics: Overviewmentioning
confidence: 86%
“…This case report is based on one subject and is a first indication that oral feeding incompetence has occurred with a single mutation of the FOXP2 gene. Additional studies are needed to confirm the hypothesis that a FOXP2 mutation may be associated with oral feeding dysfunction, much like the rigorous studies that have been completed with FOXP2 and speech impairments, and those that have shown genetic alterations during development may be associated with oral feeding competence ( Dietz et al 2012 ; Maron 2012 ; Maron et al 2012a , b , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in adults comparing the proteomic profiles of plasma and serum from the same individuals revealed a 27% similarity between biofluids (Loo et al 2010). Similarly, comparative transcriptomic analyses between umbilical cord blood and neonatal saliva revealed 40% similarity in genes expressed at the highest quintile in each biofluid (Maron et al 2012a). Saliva is also a rich source of microorganisms, including viruses, bacteria, and fungi, whose composition may serve as a window into the overall health status of an individual.…”
Section: Saliva As a Biofluidmentioning
confidence: 99%